Comparison of the Tigertriever and Self-expanding Stent Retrievers for Mechanical Thrombectomy of Acute Ischemic Stroke: A Single-center Experience - Koichiro SHINDO; Kazutaka UCHIDA; Manabu SHIRAKAWA; Shoichiro TSUJI; Shuntaro KUWAHARA; Yoji KURAMOTO; Shinichi YOSHIMURA (Neurologia Medico-Chirurgica)
Stent retrievers, including the novel Tigertriever, are important in mechanical thrombectomy for acute ischemic stroke due to a proximal large-vessel occlusion within the anterior circulation. We aimed to assess the efficacy and safety of the Tigertriever compared to self-expanding stent retrievers like EmboTrap, Solitaire, Trevo, or Tron. Patients treated at a stroke center for intracranial vessel occlusion in the anterior circulation between August 2022 and August 2024 were evaluated. The primary outcome was a modified first-pass effect, defined as a modified thrombolysis in cerebral infarction grade of 2b-3 after the first pass. Secondary outcomes included the first-pass effect, device-related serious adverse events, embolization in new territory, and hemorrhagic complications within 24 hours post-procedure. Data from 104 hemispheres in 103 patients were analyzed (24 in the Tigertriever group and 80 in the stent-retriever group). The Tigertriever group demonstrated a higher modified first-pass effect (70.8% vs. 52.5%; adjusted odds ratio 3.17; 95% confidence interval 1.06-9.47; p = 0.02). Although not statistically significant, vessel dissection (0% vs. 3.8%), subarachnoid hemorrhage (20.8% vs. 32.5%), and symptomatic intracranial hemorrhage (4.2% vs. 12.5%) within 24 hours post-procedure were lower in the Tigertriever group. No significant differences were observed in the first-pass effect or embolization in the new territory between the 2 groups. The Tigertriever might be effective for anterior circulation intracranial vessel occlusion, achieving a higher rate of modified first-pass effect. It might also be associated with minimal serious procedural complications, indicating its safety profile.